PWE-146 The Newcastle Varices In Pbc (nvp) Score – A Validation Study. (9th June 2014) - Chinnappan, L; Cross, T; Richardson, P; Martin, K; Patanwala, I
Abstract : Introduction: The NVP score 1 is a simple, non- invasive externally validated tool which aims to predict variceal risk in patients with primary biliary cirrhosis based on serum albumin levels, platelet count and serum alkaline phosphatase level. A easy accessible online tool is available where values can be entered and score greater than 50% is considered to predict the presence of varices, thereby warranting oesophago-gastro-duodenoscopy (OGD). The aim of this study was to validate this score in an external validation cohort from Liverpool. Methods: Retrospective study involving 80 PBC patients under follow up at a university hospital. Of them, patients who had undergone a OGD for any clinical reason were identified and findings of the OGD noted. Results of blood tests to allow calculation of the NVP score were recorded. An NVP probability of 0.5 was used as the cut-off to analyse the performance of the score. Results: Patients involved in the study had mean albumin levels of 36, platelets of 260 with an ALP ranging between 58 and 811. 97% were female and median age of patients was 67 years. 30 PBC patients who had an OGD were identified. 10 of the 30 patients had varices on endoscopy. The NVP Score performed well in identifying those in whom varices were absent in this cohort (sensitivity of 100%, specificity 69%, Negative Predictive Value 100% and Positive Predictive Value 10%; overall accuracy 84.5%) and had a good discriminating power with AUROC 0.89. Conclusion: The NVP Score proved to be a highly sensitive tool to discriminate patients with PBC who do not have varices and in whom OGD is unnecessary in our cohort. The study therefore strongly supports the view that prospectively applying the score in patients with PBC will help to direct endoscopic evaluation in the right category of patients thereby ensuring effective use of resources. Reference: Patanwala I, et al . J Hepatol . 2013 Aug;59(2):32735 doi:10.1016/j.jhep.2013.04:010 Disclosure of Interest: None Declared.